2005
DOI: 10.1111/j.1745-4573.2004.07103.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF ENDPOINT TEMPERATURE, pH, AND STORAGE TIME ON COOKED INTERNAL COLOR REVERSION OF PORK LONGISSIMUS CHOPS

Abstract: This project evaluated the internal cooked color changes that occurred during postcooking storage of pork loin chops (m. longissimus thoracis et lumborum, n = 120) from one of six combinations of three endpoint temperatures (71.1, 76.6 and 82.2C) and two pH groups (lower, 5.4–5.5 and higher, 5.6–5.7). Initial internal color (L*a*b*), and 24 and 48 h storage (4C) pink color development were evaluated after cooking. Although pH had no effect (P > 0.05) on initial cooked color, chops with higher pH were more red … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 13 publications
(42 reference statements)
3
5
0
Order By: Relevance
“…In addition, internal cooked redness was greater (p < 0.0001) for the BF and ST ham chops cooked to an end-point temperature of 62 • C. However, ham chops from ST were more yellow (p < 0.0001) than either BF or SM, regardless of internal temperature. Changes from red to brown of ham chops during the cooking process were greatest (p < 0.0001) in SM when cooked to an internal temperature of 73 • C. The internal cooked color results tend to agree with a previous research work [18] reporting that increased endpoint temperatures decreased the redness (a*) values for longissimus dorsi chops. It is widely known that the current results for internal cooked color are attributed to myoglobin denaturation that occurs in fresh meat during the cooking process.…”
Section: Instrumental Cooked Colorsupporting
confidence: 85%
“…In addition, internal cooked redness was greater (p < 0.0001) for the BF and ST ham chops cooked to an end-point temperature of 62 • C. However, ham chops from ST were more yellow (p < 0.0001) than either BF or SM, regardless of internal temperature. Changes from red to brown of ham chops during the cooking process were greatest (p < 0.0001) in SM when cooked to an internal temperature of 73 • C. The internal cooked color results tend to agree with a previous research work [18] reporting that increased endpoint temperatures decreased the redness (a*) values for longissimus dorsi chops. It is widely known that the current results for internal cooked color are attributed to myoglobin denaturation that occurs in fresh meat during the cooking process.…”
Section: Instrumental Cooked Colorsupporting
confidence: 85%
“…In another study, pork loin chops of 2 pH groups (pH 5.4 to 5.5, pH 5.6 to 5.7) cooked to 3 endpoint temperatures could not be separated by their Hunter values immediately after cooking (Mancini and others 2005). The small difference in pH between these groups could be one explanation, as could the high (>71 °C) temperatures studied.…”
Section: The Influence Of Phmentioning
confidence: 95%
“…Lytras, King, and Ledward (2000) studied the kinetics of Mb denaturation in beef and lamb burgers cooked to wide range of internal temperatures and observed that Mb denaturation follows a first order kinetics. Several studies documented increased Mb denaturation in meats as internal cooking temperatures increased (Bernofsky et al, 1959;Machlik, 1965, Nusimovich, Celmi, & Pagliaro, 1979Howe, Gullett, & Usborne, 1982;Bowers et al, 1987;Trout, 1989;Hague et al, 1994;Lavelle, Hunt, & Kropf, 1995;Hunt, Sorheim, & Slinde, 1999;Mancini, Kropf, Hunt, & Johnson, 2005).…”
Section: Biochemistry Of Cooked Meat Pigmentsmentioning
confidence: 99%